The effective distance and cooling rate of liquid nitrogen-based adjunctive cryotherapy for bone tumors ex vivo. Issue 8 (7th June 2022) - Chang, Yu-Chuan; Chao, Kuang-Yu; Chen, Chao-Ming; Chen, Cheng-Fong; Wu, Po-Kuei; Chen, Wei-Ming
Abstract : Background: Liquid nitrogen (LN) has been used as an adjuvant cryotherapy for bone tumors including giant-cell tumor of the bone (GCTB) to remove residual tumor cells after curettage. This study evaluated variables related to the efficacy of LN-based cryoablation in the context of adjuvant treatment of GCTB using porcine femur bone model. Methods: A porcine femur bone model was adopted to simulate intralesional cryotherapy. A LN-holding cavity (point 1, nadir) in the medial epicondyle, 4 holes (points 2–5) in the shaft situated 5, 10, 15, and 20 mm away from the proximal edge of the cavity, and 2 more holes (points 6 and 7) in the condyle cartilage (10 and 20 mm away from the distal edge of the cavity) were made. The cooling rate was compared between the 5 points. The cellular morphological changes and DNA damage in the GCTB tissue attributable to LN-based cryotherapy were determined by H&E stain and TUNEL assay. Cartilage tissue at points 6 and 7 was examined for the extent of tissue injury after cryotherapy. Results: The temperature kinetics at points 1, 2 reached the reference target and were found to be significantly better than the reference (both p < 0.05). The target temperature kinetics were not achieved at points 4 and 5, which showed a significantly lower cooling rate than the reference (both p < 0.001) without reaching the –60°C target. Compared with untreated samples, significantly higher proportion of shrunken or apoptotic cells were found at points 1–3; very small proportion were observed at points 4, 5. Significantly increased chondrocyte degeneration was observed at point 6, and was absent at point 7. Conclusion: The cryotherapy effective range was within 5 mm from nadir. Complications were restricted to within this distance. The cooling rate was unchanged after three repeated cycles of cryotherapy.